Disorders Involving a Persistent Craniopharyngeal Canal: A Case Series - Poonia, Seerat K.; Cazzador, Diego; Kaufman, Adam C.; Kohanski, Michael A.; Kuan, Edward C.; Tong, Charles C. L.; Carlson, Roy D.; Borsetto, Daniele; Emanuelli, Enzo; Palmer, James N.; Adappa, Nithin D. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives A persistent craniopharyngeal canal (CPC) is a rare embryologic remnant that presents as a well-corticated defect of the midline sphenoid body extending from the sellar floor to the nasopharynx. Our case series aims to describe three unique presentations of this congenital anomaly and their subsequent management.Design Retrospective review.Setting Tertiary academic medical center.Participants Patients who underwent endoscopic transnasal surgical repair of a CPC lesion.Main Outcome Measures Resolution of symptoms and surgical outcomes.Results A total of three patients were identified. The clinical presentation varied, however, all cases prompted further imaging which demonstrated a persistent CPC and associated pathologic lesion. The presentation of a persistent CPC with nasal obstruction and subsequent iatrogenic cerebrospinal fluid leak as in Case 1 demonstrates the importance of imaging in this work-up. Cases 2 and 3 in the series were representative of the larger subset of patients in the literature who present with the defect incidentally but still warrant surgical management. Nonetheless, a standard approach to diagnosis with preoperative imaging and subsequent transnasal endoscopic repair of the skull base defect was undertaken.Conclusion The persistent CPC is a rare congenital anomaly associated with diverse pathology and careful review of preoperative radiology is critical to the management. When warranted, subsequent surgical repair and reconstruction is associated with excellent postoperative outcomes.
Keywords: craniopharyngeal canal; congenital; endoscopic; skull base; surgery; cerebrospinal fluid